A practical strategy for using miniature chromatography columns in a standardized high‐throughput workflow for purification development of monoclonal antibodies. (20th March 2014) - Welsh, John P.; Petroff, Matthew G.; Rowicki, Patricia; Bao, Haiying; Linden, Thomas; Roush, David J.; Pollard, Jennifer M.
<x xml:space="preserve">Abstract</x> The emergence of monoclonal antibody (mAb) therapies has created a need for faster and more efficient bioprocess development strategies in order to meet timeline and material demands. In this work, a high‐throughput process development (HTPD) strategy implementing several high‐throughput chromatography purification techniques is described. Namely, batch incubations are used to scout feasible operating conditions, miniature columns are then used to determine separation of impurities, and, finally, a limited number of lab scale columns are tested to confirm the conditions identified using high‐throughput techniques and to provide a path toward large scale processing. This multistep approach builds upon previous HTPD work by combining, in a unique sequential fashion, the flexibility and throughput of batch incubations with the increased separation characteristics for the packed bed format of miniature columns. Additionally, in order to assess the applicability of using miniature columns in this workflow, transport considerations were compared with traditional lab scale columns, and performances were mapped for the two techniques. The high‐throughput strategy was utilized to determine optimal operating conditions with two different types of resins for a difficult separation of a mAb monomer from aggregates. Other more detailed prediction models are cited, but the intent of this work was to use high‐throughput strategies as a general guide for scaling and assessing operating space rather than as a precise model to exactly predict performance. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:626–635, 2014